Significant Decrease in Pertactin-Deficient Bordetella pertussis Isolates, Japan - Yukihiro Hiramatsu; Yusuke Miyaji; Nao Otsuka; Yoshichika Arakawa; Keigo Shibayama; Kazunari Kamachi (Emerging Infectious Diseases, 2017)
Prevalence of pertactin-lacking Bordetella pertussis isolates has been observed worldwide. In Japan, however, we found that the frequency of pertactin-deficient isolates in 2014–2016 (8%) was significantly lower than the frequency in 2005–2007 (41%), 2008–2010 (35%), and 2011–2013 (25%). This reduction was closely associated with changes in genotypes.